MCF pathogenesis: studies on the replication and tropism of ovine herpes virus 2 (OvHV-2) in peripheral blood mononuclear cells of ruminants - Tsibane, Matshediso (Tshidi) L., author; DeMartini, James C., advisor; Callan, Robert J., advisor; Blair, Carol D., committee member; Carlson, Jonathan, committee member; Akkina, Ramesh, committee member (Colorado State University. Libraries, 2006)
The pathogenesis of ovine herpesvirus 2 (OvHV-2), the causative agent of malignant catarrhal fever (MCF) is unknown. Based on clinical status, OvHV-2 infected animals can be divided into 4 groups, namely, asymptomatic sheep, subclinically infected, clinically affected, and recovered cattle. To examine the role of OvHV-2 load and tropism on clinical status, peripheral blood mononuclear cells (PBMCs), obtained from animals in each of the 4 groups were immunomagnetically sorted into CD2+, CD3+, CD4+, CD8+, and γδ+ T-cell, B-cell, and monocyte subsets. The role of OvHV-2 load and tropism on clinical status was examined by investigating and comparing OvHV-2 DNA copy numbers in total PBMCs and PBMC subsets between and within the 4 groups of animals. Flow-cytometry was used to determine sorted subset percentages within each group to examine the effects of OvHV-2 infection on PBMC subset percentages. PBMC subset percentages from non-infected cattle were additionally examined. There was no difference in the OvHV-2 tropism between the 4 groups. T-cells were preferentially infected over B-cells and monocytes in all groups. Clinically affected cattle had significantly higher OvHV-2 genome copy numbers in their total PBMCs compared to the other groups. There was no association between OvHV-2 infection status and changes in PBMC subset percentages. Differences in viral DNA copy numbers within total PBMCs of the 4 groups are suggestive of a role for viral DNA replication on clinical status. OvHV-2 positive T-cell lymphoblastoid cell lines (LCLs) established from recovered and fatal cases of MCF displayed variable cellular and OvHV-2 replication kinetics. Although all the LCLs harbored predominantly latent OvHV-2 genome, DNase protected and unprotected OvHV-2 genomes were present in the LCL supernatants and all the LCLs supported transcription of messenger RNA to a late viral structural gene. Establishment of an LCL from a recovered case of MCF suggests a persistently latent infection of T-cells within recovered cases. Treatment of LCLs with several chemicals displayed variable effects on OvHV-2 DNA replication. Dexamethasone treatment may lead to an increase in intracellular viral burden, whereas, acyclovir may successfully decrease OvHV-2 DNA copy numbers. Both of these chemicals may impact supportive MCF therapy.
Keywords: microbiology; anatomy and physiology; animals; immunology